Proposta de aplicação de dispositivos de Internet of Things (IoT) integrados a plataforma FIWARE como ferramentas para telegestão de equipamentos médicos oftalmológicos - Macedo, Rubens Aparecido Pereira De [UNIFESP] (2020)
Objective: To evaluate and establish the necessary requirements for the consolidation of the Proposed Application of Internet of Things (IoT) Devices Integrated into the FIWARE Platform as tools for the Telemanagement of Ophthalmic Medical Equipment. Methods: This research work was developed within the Health Technological Innovations Laboratory and validated by the Department of Ophthalmology and Visual Sciences of the Federal University of São Paulo. For this purpose, the elaboration phases were established according to the criteria of the project management technique called Systems Engineering Systems Engineering, which organizes and systematizes interdisciplinary actions, involving: process evaluation, organization of complex systems and interrelation of people and technologies. Studies on the requirements regarding the applicability of the FIWARE Platform strictly followed the technical compatibility analyzes required by the regulatory authorities for this technology and its application in the health area (ANVISA and ABNT), seeking to achieve state of the art with the application of technologies. innovations within the Brazilian health area. Result: This work has been able to safely validate the FIWARE Platform's ability to meet the proposed requirements. It was also possible to validate the application of integrated technologies; Electronic devices, IoT connectivity, software platform and presentation model of the information generated are within the required quality and effectiveness standards. Conclusion: It was possible to validate the FIWARE Platform and find that it meets the necessary requirements to be recommended as a technological solution for remote management (telemanagement) of ophthalmic medical equipment.